India Systematic Country Diagnostic : Realizing the Promise of Prosperity - World Bank Group (World Bank, Washington, DC, 2018)
With one of the world’sfastest-growing economies, India is a brightspot in a lackluster global environment. In the past three decades, per capita incomes have quadrupled, poverty has retreated, illiteracy rates have tumbled, and health conditions have improved. An expanding economy has provided the much-needed resources to address chronic infrastructure deficits and improve the lives ofmillions. India is now poised to transition to a higher and more widely shared level of prosperity: by 2047—the centenary of independence—most citizens could join the ranks of the global middle class. Households in the global middle class can fulfill a range of aspirations, such as safe and affordable housing, health care, education, clean water, sanitation facilities, reliable electricity, a safe environment, and discretionary income to spend on leisure pursuits. Achieving these goals requires incomes well above the extreme poverty line, as well as vastly improved levels of public service delivery. Projections suggest that for this to occur, rapid growth (of 8 percent or more) will need to be sustained for approximately the next three decades. And while the promise of amiddle classIndia may appear to be tantalizingly close,success is not necessarily pre-ordained. Most countries that grew rapidly in one decade, decelerated in the next. In East Asia, for example, growth traps appear to have emerged from a shortage of low-wage labor, partly a consequence of demographic change. Growth slowdowns in Latin America and Africa’s mineral-dependent economies have mirrored commodity price cycles. India’s economic constraints are different. Unlike East Asia, there is an expanding share of young adults in India, so there is limited risk of sustained wage increases for lowskilled workers. And unlike Latin America, India is a net importer of minerals, timber, and many other commodities, so that India’s growth does not fade with declining commodityprices. India is distinctive in other ways too. It’s size and immense diversity suggest the need for remedies that fit its particular circumstances. Space age industries, high-tech agriculture and elite colleges thrive alongside primitive workshops, subsistence farms and schools that impart little knowledge. Prosperity and poverty also live side-by-side. India is simultaneously home to the 3rd largest number of billionaires in the world, together with the highest number of poor people in the world. As a result, policy reforms must navigate this considerable diversity, take into account the scale of the country, and respect a robust administrative culture that requires change to be indigenized and contested in order to be acceptable. The accompanying volume 2 of the SCD provides a summary of the main comments and debatesthat ensued during the review and consultation process of this document.